The Effect of Cucumber Juice (Cucumis Sativus) Toward Hypertension of Elderly at Tresna Werdha Budi Sejahtera Social Institution of Banjarbaru South Borneo 2017 - Candra Kusuma Negara; Erna Erna; Anna Anna (IJNP (Indonesian Journal of Nursing Practices), 2018)
AbstractIntroduction: Hypertension is a degenerative disease that becomes a major problem in society, especially elderly. Hypertensioncauses complications of cerebral hemorrhage, heart failure, kidney failure, and blindness due to rupture of blood vessels.Objective: Analyze the effect of cucumber juice on blood pressure in elderly with hypertension  at Tresna Werdha Budi Sejahtera Social Institution of Banjarbaru South Borneo 2017.Method: Quasi experiments with Ones group pre-post test design. Total of samples are 35 people taken using purposive sampling technique. Normality test using Shapiro-wilk and statistical analyze using Paired t-test. 200g of cucumber juice mix on 100 ml water, drink twice a day during morning and afternoonResult: Systolic blood pressure decreased after cucumber juice therapy with 149,68 mmHg to 136.65 mmHg and p value 0.00 (p0.05)  and  diatolic blood pressure decreased after cucumber juice therapy  with 95.99 mmHg to 80.09 mmHg and p value p-=0,000. Diastolic blood pressure after giving cucumber juice was 89,08 mmHg (± 3,355 mmHg), lower than diastolic blood pressure before giving cucumber juice which is 95,88 mmHg (± 3,332 mmHg). Conclusion: Cucumber juice can lower blood pressure in elderly hypertension patients.